A cell adhesion-promoting multi-network 3D printing bio-ink based on natural polysaccharide hydrogel - Qi, Yong; Zhang, Shuyun; He, Yanni; Ou, Shuanji; Yang, Yang; Qu, Yudun; Li, Jiaxuan; Lian, Wanmin; Li, Guitao; Tian, Junzhang; Xu, Changpeng (Frontiers in Bioengineering and Biotechnology, 2022)
Due to its high biosafety, gellan gum (GG) hydrogel, a naturally occurring polysaccharide released by microorganisms, is frequently utilized in food and pharmaceuticals. In recent years, like GG, natural polysaccharide-based hydrogels have become increasingly popular in 3D-printed biomedical engineering because of their simplicity of processing, considerable shear thinning characteristic, and minimal pH dependence. To mitigate the negative effects of the GG's high biological inertia, poor cell adhesion, single cross-linked network, and high brittleness. Mesoporous silica nanospheres (MMSN) and Aldehyde-based methacrylated hyaluronic acid (AHAMA) were combined to sulfhydrated GG (TGG) to create a multi-network AHAMA/TGG/MMSN hydrogel in this study. For this composite hydrogel system, the multi-component offers several crosslinking networks: the double bond in AHAMA can be photocrosslinked by activating the photoinitiator, aldehyde groups on its side chain can create Schiff base bonds with MMSN, while TGG can self-curing at room temperature. The AHAMA/TGG/MMSN hydrogel, with a mass ratio of 2:6:1, exhibits good cell adhesion, high strength and elasticity, and great printability. We believe that this innovative multi-network hydrogel has potential uses in tissue regeneration and biomedical engineering.